Odcięte stopy, odpiłowane kopyta… W kręgu rozważań nad metodami badań archeologicznych śladów obrzędowości funeralnej dawnych Słowian - Kajkowski, Kamil (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2024)
The research potential of archaeology in investigating ancient religiosity remains a topic of enduring debate involving both proponents, sceptics and (hyper)critics of the validity of such an approach. The result of this discourse is the emergence of a separate research discipline: archaeology of religions. It has developed its own technique to better understand and interpret traces of ritual practices. However, the research methods used by archaeologists of religion are still not widely applied to the studies of early medieval Slavdom. Clearly, there have been difficulties in understanding phenomena that escape the methods of traditional archaeology. These phenomena include horse burials found within sepulchral areas. While all these objects show a number of similarities to human graves interpreted as atypical and perceived as evidence of ritual activities, they are generally considered to be either alien to Slavic communities or a manifestation of utilitarian activities. What is forgotten is that both phenomena were identified in cemeteries, i.e. areas characterised by the sacred thus, by definition, dedicated to the celebration of various ritual scenarios, whether related to the burial sphere or to images of eschatological nature. The aim as set out by the author of this article is to compare the two types of objects and to determine whether the place and manner of their deposition and the diagnostic features associated with them are different enough to link the former with abstract thinking and the latter with utilitarian practices.